Need for an alternative educational approach to make Muslims responsible for the social world - Rahath House, Yousef (2013)
This article is an effort to look at the contemporary Islamic educational practice from a perspective that relates education with social responsibility. The central concern of the article is to emphasize the importance of education in enabling Muslim youth to address the issue of social responsibility. It has been assumed that due to the negligence of social dimension of Islam, most of the contemporary Islamic educational institutions are incapable of enabling Muslim youth in looking at the historical context of their lived reality more critically. Consequently majority of the Muslims are not bothered about several concrete human social problems such as inequality, economic exploitation and fragmentation of the community into different classes and groups. To solve this issue, we need a new educational approach that emphasizes the social dimension of Islam. Since the Quran portrays human being as a social being by highlighting his various responsibilities in this world, one of the guiding principles of Islamic education should be to make Muslims capable of understanding the world for making it more just and better. Based on this argument, contemporary Islamic educational practices have been evaluated and it was found that a number of changes are needed in the Islamic educational practice.